THE EFFECTIVENESS OF USE OF MULTI REPRESENTATION-BASED TEACHING MATERIALS IN SCIENCE LEARNING IN JUNIOR HIGH SCHOOL: SYSTEMATIC LITERATURE REVIEW - Sulystia Angelina; Susilawati Susilawati; Niki Dian Permana; Rian Vebrianto (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Student inability to multi-representation in science learning in junior high school and teacher ability to provide teaching materials according to the characteristics of students who have difficulty in multi-representation causes the learning process cannot achieve the desired results. It affects the low learning outcomes and students' cognitive abilities. Therefore, this study aims to determine the types of multi-representation-based teaching materials in science learning in junior high schools and the effectiveness of using multi-representation-based teaching materials used in science learning in junior high schools. The method used is systematic literature review using PRISMA diagrams. The database used to search for literature uses two digital libraries, namely Google Scholar and Garuda. For the selected literature to be relevant, it uses the keyword teaching materials and multi-representation. The next step is to get scientific articles published from 2016 to 2021 which discuss the use of multi-representation-based teaching materials in science learning in junior high schools. The results of the scientific article search contained eight articles that would be analyzed and synthesized. The analytical technique used is the narrative method by grouping the extracted data. The results show the types of multi-representation-based teaching materials in science learning are printing and non-printing teaching materials. Printed teaching materials are modules, books, and worksheets, while non-printed teaching materials are in the form of web simulations. The use of multi-representation-based teaching materials has proven to be effective in the science learning process in junior high schools.